Evaluasi Desain Antar Muka Website Dinas Koperasi Kota Malang Menggunakan Heuristic Evaluation - Andrew Wise Jeremia; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The purpose of this study was to determine the usability problems and severity values ​​contained in the Department of Cooperative dinkop.malangkota.go.id Malang by using heuristic evaluation and recommendations on the way down. The method used is the heuristic evaluation method in finding problems through observation or opinion by IT experts who have skills in the content field of the application. The survey results revealed that usability problems found using the heuristic evaluation there were 24 issues totaling entirety. Of the total of 24 issues divided unevenly in each heuristic for most issues contained in the H5-Consider heuristic error-prone conditions, namely